IDENTIFICATION OF PYRITE VALENCE BAND CONTRIBUTIONS USING SYNCHROTRON-EXCITED X-RAY PHOTOELECTRON SPECTROSCOPY - Nesbitt H.W.; Harmer S.L.; Berlich A.G.; Uhlig I.; Szargan R.; Bancroft G.M. (My University, 2004)
The major contributions to the pyrite valence band have been identified experimentally by monitoring XPS valence band signal intensity as a function of photon (X-ray source) energy. The S-S σ and σ* orbitals are located at about 13 and 16 eV binding energy and are almost exclusively derived from S 3s-S 3s mixing; there is no experimental evidence for a S 3p contribution to these molecular orbital (molecular orbital) values as required for sp3 hybridization. Fe-S σ (Fe 3deg-S 3pz derived) and Fe-S π and π* (Fe 3dt2g-S 3pxy derived) molecular orbitals are identified at Binding Energies (B.E.) less than 8 eV, and are consistent with energies calculated by Eyert et al. (1998). Fe-S π molecular orbital contributions are located in the valence band between about 1.8 and 3 eV and Fe-S π* molecular orbitals contribute between about 0.7 to 1.5 eV binding energy. Contributions observed at the top of the valence band and concentrated between the Fermi level and about 0.6 eV B.E. may be derived from Fe 3deg (non-bonding) orbitals. The experimental data are consistent with these non-bonding contributions being derived from surface Fe species (Fe electronic surface states), and perhaps represent the Fe 3deg "dangling bonds" produced by rupture of Fe-S σ bonds during fracture. The conformity of spectral assignments based on experimental data with band theoretical calculations (of Eyert et al. 1998, using a basis set appropriate to pyrite) indicates that the essential aspects of the pyrite valence band are understood and energetically quantified. Additional study is required to identify positively quently the least stable electronic states contributing to the top of the outer valence band. Furthermore, they are most likely to be detected in spectra collected at 30 to 100 eV where surface state contributions approach 40 to 50% of total signal (Leiro et al. 1998; Schaufuss et al. 2000; Nesbit et al. 2000; Nesbitt et al 2002). The hypothesis requires confirmation.
Keywords: pyrite